A Simple Dynamic Signal Analyzer Virtual Instrument to Monitoring and Control Airflow Temperature - Asmara Yanto; Anrinal; Ryan Adi Pratama (Jurnal Teknik Mesin, 2016)
This work aims to present a Dynamic Signal Analyzer Virtual Instrument (DSA-VI) for monitoring and control the airflow temperature in a prototype of air duct. Here, the DSA-VI has developed by using LabVIEW software and Arduino UNO. To investigate the performance of DSA-VI, an experiment has performed to monitoring and control airflow at settling temperature, 40oC, 50oC, and 60oC, respectively by using the DSA-VI. By assuming that an airflow temperature control system as the first order system, the time constant () should be inspected as one of the system characteristics. The testing at the settling and surrounding temperatures (Tsp and T0) are 40oC and 28.81oC respectively, obtained value of  is 7.49 s; at Tsp and T0 are 50oC and 29.88oC respectively, obtained value of  is 11.35 s; and at Tsp and T0 are 60oC and 28.81oC respectively, obtained value of  is 19.54 s. By using DSA-VI, the value of  at the transient response can be evaluated. At the steady state response, the airflow temperature has controlled well with the steady state error less than ± 2.5 %.